Ethics and governance for internet‐based conservation science research. Issue 6 (7th July 2021) - Thompson, Ruth M.; Hall, Jordan; Morrison, Chris; Palmer, Nicole R.; Roberts, David L.
Abstract: Internet‐based research is increasingly important for conservation science and has wide‐ranging applications and contexts, including culturomics, illegal wildlife trade, and citizen science. However, online research methods pose a range of ethical and legal challenges. Online data may be protected by copyright, database rights, or contract law. Privacy rights may also restrict the use and access of data, as well as ethical requirements from institutions. Online data have real‐world meaning, and the ethical treatment of individuals and communities must not be marginalized when conducting internet‐based research. As ethics frameworks originally developed for biomedical applications are inadequate for these methods, we propose that research activities involving the analysis of preexisting online data be treated analogous to offline social science methods, in particular, nondeceptive covert observation. By treating internet users and their data with respect and due consideration, conservationists can uphold the public trust needed to effectively address real‐world issues. Abstract : Article impact statement : Conservationists undertaking internet‐based research should do more to avoid ethical and legal backlash from users and service providers. Abstract : Ética y Gestión para la Investigación Científica de la Conservación Basada en Internet Resumen: La investigación basada en internet es cada vez más importante para las ciencias de la conservación, además de tener contextos y aplicaciones de gran alcance como el análisis de textos, el mercado ilegal de fauna y la ciencia ciudadana. Sin embargo, los métodos de investigación en línea representan una gama de retos éticos y legales pues los datos virtuales pueden estar protegidos por derechos de autor, derechos de base de datos o leyes contractuales. Además, los derechos de privacidad pueden restringir el uso y el acceso a los datos, así como también los requerimientos éticos impuestos por las instituciones. Los datos virtuales tienen valor en el mundo real y el tratamiento ético de los individuos y de las comunidades no se debe marginalizar cuando se realiza una investigación por internet. Ya que los marcos éticos desarrollados originalmente para aplicarse en temas biomédicos son inadecuados para estos métodos, proponemos que las actividades de investigación que involucran el análisis de los datos virtuales preexistentes sean tratadas como análogas a los métodos no virtuales de las ciencias sociales, especialmente la observación encubierta no engañosa. Si se trata a los usuarios del internet y a sus datos con respeto y la consideración debida, los conservacionistas pueden mantener la confianza pública necesaria para tratar efectivamente los asuntos del mundo real.